VD_FINDINFO Jug / 2020 / 113 vom 19. März 2020 - VD Tribunal cantonal (2020)
DÉTENTION POUR DES MOTIFS DE SÛRETÉ, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. c CPP (CH), 233 CPP (CH)